Education Effectivity in Increasing Adolescent’s Female Awareness in Preventing Anemia - Maulidya Faatihah Rizqii Riswanto; Amalia Rahma; Eka Srirahayu Ariestiningsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescents are more susceptible to anemia resulting from iron deficiency. Diverse initiatives have been implemented to reduce the incidence of anemia, which is rising annually. The undertaken efforts do not instantaneously convert an individual into an expert in anemia prevention. This study seeks to determine young women's knowledge and self-awareness levels, along with the factors that affect self-awareness. The design of this study was quasi-experimental, employing a distinct sample for the pretest and posttest. This study was carried out in SMAN 1 Kebomas from July to September 2024, with participants who matched the inclusion criteria. The study sample comprised 79 individuals selected through a purposive sampling method. The instruments used to conduct research were questionnaires, which was adopted from previous similar researchers and and have been retested with a reliability test result of 0.818 namely about knowledge before and after education, and strengthening self-awareness to prevent anemia. The Paired T-test and Linear Regression were employed for analysis. The study indicates a significant difference in the average levels of knowledge and self-awareness, with a p-value of 0.000 < 0.05. The data indicates a significant correlation between family support and self-awareness, with a p-value of 0.03 < 0.05, as well as between peer support and self-awareness, with a p-value of 0.01 < 0.05. The provision of education can enhance the understanding and self-awareness of young women, bolstered by diverse sources of information, particularly familial and peer support.